Responding to the Global Food Crisis - Three perspectives: IFPRI 2007-2008 Annual Report Essay - von Braun, Joachim; Sheeran, Josette; Ngongi, Namanga (International Food Policy Research Institute, 2008)
The dramatic rise and volatility of food prices over the last year have shaken the global food system. Governments and the international development community generally have responded to various aspects of the food crisis, but questions remain about whether the right actions are being pursued, how best to respond, and what the future holds. The three essays here by Namanga Ngongi, president of the Alliance for a Green Revolution in Africa, Josette Sheeran, executive director of the World Food Programme, and Joachim von Braun, director general of the International Food Policy Research Institute, respond to these critical questions. They point to the dangers and pitfalls of misguided policies, but also to the very real opportunities for responding in a way that prevents future crises and assures food security now and in the long term.